2017
DOI: 10.1093/brain/awx224
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cerebrovascular disease on brain networks in prodromal and clinical Alzheimer’s disease

Abstract: Little is known about the interaction between Alzheimer’s disease and cerebrovascular disease with respect to network degeneration. Chong et al. demonstrate differential functional and structural network changes in patients with Alzheimer’s disease with and without cerebrovascular disease, suggesting that the two groups may have different underlying pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 52 publications
5
61
1
Order By: Relevance
“…The main symptoms of PSD include negative emotions, cognitive deficits and physical symptoms. The default mode network, dorsal attention network, and the salience network have been shown to be the "hub" of different depression subtypes (2)(3)(4). Neuroimaging evidence from our studies and others have identified the structural and functional network disruption in post-stroke depression and other neurological diseases (2,5,6).…”
Section: Introductionsupporting
confidence: 52%
“…The main symptoms of PSD include negative emotions, cognitive deficits and physical symptoms. The default mode network, dorsal attention network, and the salience network have been shown to be the "hub" of different depression subtypes (2)(3)(4). Neuroimaging evidence from our studies and others have identified the structural and functional network disruption in post-stroke depression and other neurological diseases (2,5,6).…”
Section: Introductionsupporting
confidence: 52%
“…Participants. We studied 124 AD, 103 aMCI, and 49 HC from an ongoing project, recruited from memory clinics in the National University Hospital, Saint Luke's Hospital and nearby communities 52,53 . Diagnoses were made by psychologists, neurologists, and research personnel at weekly consensus meetings based on clinical observation, lab tests (e.g., blood test), neuroimaging scans and neuropsychological assessments.…”
Section: Methodsmentioning
confidence: 99%
“…Data pre-processing. fMRI data were pre-processed with a standard pipeline using the FMRIB Software Library (FSL) 56 and Analysis of Functional NeuroImages software (AFNI) 57 as described previously 36,53 . Briefly, pre-processing of the structural images included reducing nonlinear image noise (SUSAN), extracting brain tissue (skull stripping, BET), normalizing to the Montreal Neurological Institute (MNI) 152 standard space (FLIRT/FNIRT) and segmenting into grey matter (GM), white matter (WM) and cerebrospinal fluid (CSF).…”
Section: Clinical and Neuropsychological Assessments The Montreal Comentioning
confidence: 99%
“…This study recruited participants from two independent datasets: (a) 75 NCI and 104 MCI who were new patients from the Alzheimer's Disease Neuroimaging Initiative (ADNI2) study as defined on July 10, 2018 and (b) 20 NCI and 93 MCI from Memory Aging and Cognition Centre (MACC) dataset recruited from memory clinics/community in Singapore (Chong et al, ). ADNI data were obtained from the ADNI database (http://adni.loni.usc.edu/).…”
Section: Methodsmentioning
confidence: 99%